1991
DOI: 10.1111/j.1600-0536.1991.tb01851.x
|View full text |Cite
|
Sign up to set email alerts
|

Nickel concentrations in fingernails as a measure of occupational exposure to nickel

Abstract: The nickel concentration in fingernails from 2 groups of people occupationally exposed to nickel was determined. In one group, comprising 83 persons moderately exposed to nickel, the mean +/- standard deviation (SD) was 29.2 micrograms/g +/- 56.7 micrograms/g and the median 13.8 micrograms/g (range 0.926-396 micrograms/g). In the other group, comprising 51 persons heavily exposed to nickel, the mean +/- SD was 123 micrograms/g +/- 289 micrograms/g and the median 29.9 micrograms/g (range 1.95-1770 micrograms/g)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 6 publications
0
16
0
1
Order By: Relevance
“…A Danish occupational study found the relative Ni fingernail concentrations to be higher among heavily exposed workers (median 29.9 μg/g) than among moderately exposed workers (median 13.8 μg/g), 17 and in turn were much lower among a control group (median 0.49 μg/g). On the other hand, a reference study in Detroit, Michigan, showed the median concentration of Ni in non-exposed subjects’ toenails to be 37.4 μg/g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Danish occupational study found the relative Ni fingernail concentrations to be higher among heavily exposed workers (median 29.9 μg/g) than among moderately exposed workers (median 13.8 μg/g), 17 and in turn were much lower among a control group (median 0.49 μg/g). On the other hand, a reference study in Detroit, Michigan, showed the median concentration of Ni in non-exposed subjects’ toenails to be 37.4 μg/g.…”
Section: Discussionmentioning
confidence: 99%
“…9 In particular, toenail As concentrations have been shown to be a good biomarker of environmental exposure to As. 1012 The concentration of Cr in toenails has also been used as a biomarker of exposure in epidemiologic studies, 1315 as well as concentrations of Ni in toenails 16 and fingernails, 17 although to a lesser extent than As or Cr.…”
Section: Introductionmentioning
confidence: 99%
“…Following sampling, the nickel content is analysed, for example, by inductively coupled plasma mass spectrometry. Measurements of nickel nail deposits in individuals with suspected occupational exposure to nickel was used in combination with elicitation thresholds to define occupational exposure with a cut‐off value of 8 μg of nickel per gram . Finger immersion has been used to evaluate nickel skin exposure in different occupations .…”
Section: Exposure Quantificationmentioning
confidence: 99%
“…(28) In Mortada et al, (42) Pb was measured in toenail samples taken from police officers exposed to traffic pollution, which were significantly associated with increased markers of nephrotoxicity. Higher Ni concentrations have been found in the fingernails of welders (43) and other metal workers. (25) A recent study in rats found that exposure to Mn in welding fumes was correlated with manganese concentration in nails, as well as Mn accumulation in dopaminergic brain areas, (44) indicating that toenail metal concentration may reflect neurotoxicant deposition in the brain.…”
Section: Introductionmentioning
confidence: 98%